A facile, fast responsive and highly selective mercury(ii) probe characterized by the fluorescence quenching of 2, 9-dimethyl-1, 10-phenanthroline and two new metal–organic frameworks. Issue 70 (12th July 2016) - Shan, Fa-Shuo; Lai, Jia-Ping; Sun, Hui; Zhang, Ping; Luo, Chong; He, Yan-Hui; Feng, Huan-Ran
Abstract : A fast responsive and highly selective mercury(ii ) sensor was developed using the fluorescence quenching mechanism of 2, 9-dimethyl-1, 10-phenanthroline (2, 9-DMP) towards mercury(ii ). Abstract : A fast responsive and highly selective mercury(ii ) sensor was developed using the fluorescence quenching mechanism of 2, 9-dimethyl-1, 10-phenanthroline (2, 9-DMP) towards mercury(ii ). Furthermore, two kinds of metal–organic frameworks (MOFs) of 2, 9-DMP–Hg(ii ) have been synthesized and characterized by X-ray diffraction. The probe 2, 9-DMP exhibited a fast and highly selective response to mercury(ii ) ions in aqueous solution, showing a good linear relationship over the concentration range of 0.050–2.0 μM for Hg(ii ) with R 2 = 0.9994. The established procedure was used to monitor the concentration of mercury(ii ) in drinking water and Zhujiang River water samples with satisfactory recoveries of 85.42–101.5% and 81.72–96.09%, respectively. Furthermore, the fluorescence quenching mechanism of 2, 9-DMP by mercury(ii ) was investigated and clarified by the data of single crystal X-ray diffraction of MOFs and the Job's plot analyses of 2, 9-DMP towards Hg(ii ).